Improved accuracy of atomic nitrogen detection in plasma by high-intensity fs-TALIF calibrated using VUV absorption spectroscopy - Brisset, A.; Pascual-Fort, C.; Minesi, N. Q.; De Oliveira, N.; Stancu, G. D. (Frontiers in Physics, 2025)
This paper is devoted to improving the accuracy of the calibration method employed for femtosecond Two-photon Absorption Laser-Induced Fluorescence (fs-TALIF) diagnostics operating in a high laser intensity regime, i.e., TW.cm-2. Due to the extreme instantaneous intensity and mode-locked laser features, the fluorescence signal depends not only on the populations of the ground and excited states of the probed atomic radical, but also on phenomena such as Stark detuning and coherent excitation. Rate equations are no longer valid and therefore, the calibration is performed here using a source of the same atomic species of interest with a known absolute density. For atomic nitrogen, the reference source is based on a homogenous, steady-state DC plasma. Its absolute density is measured in specific operating conditions by Vacuum UltraViolet (VUV) absorption spectroscopy using a high-resolution Fourier Transform Spectrometer (FTS). The uncertainty of nitrogen density measured via VUV absorption was found to be less than 20% when selecting non-saturated absorption lines and plasmas with negligible molecular absorption background. The detection limit and accuracy for nitrogen density using fs-TALIF in a high laser intensity regime were determined to be 1012 cm-3 and 25%, respectively, which represents a significant improvement over the quadratic regime method using conventional noble gas calibration. The fluorescence calibration was proven for plasma conditions with pressure and nitrogen density varying by about one order of magnitude and was found to be quench-free. The laser spectral profile was Fourier-limited and the two-photon absorption profile was dominated by the laser broadening mechanism. Comparison of two femtosecond systems sharing the same laser pump, detection, beam waist and laser power showed an important difference in fluorescence yields. This was attributed to spectral dispersion affecting the temporal laser intensity profiles, which consequently altered the two-photon absorption probability.